Coexistence of martensite and strain glass phases in homogenized Ni-rich TiNi shape memory alloys. (June 2019) - Bag, Pallab; Chang, Pei-Chi; Kuo, Yung-Kang; Wu, Shyi-Kaan; Lin, Chieh; Li, Bo-Yi
Abstract: The transport and thermal properties of homogenized Ti50- x Ni50+ x shape memory alloys (SMAs) in the range of 1.0 ≤ x ≤ 1.3 (in at. %) by means of electrical resistivity, Seebeck coefficient, thermal conductivity, and heat capacity measurements are presented. From the electrical resistivity measurement, we have observed thermal hysteresis in cooling and subsequent warming curves for x = 1.1 to 1.2 suggesting the occurrence of a martensitic transition. The martensitic transition is also detected in the Seebeck coefficient, thermal conductivity, and heat capacity measurements in these alloys. Despite this, the x = 1.2 alloy shows a negative temperature coefficient of resistivity over the entire temperature range under investigation, indicating the formation of strain glass phase at low temperatures. The existence of the strain glass state is confirmed by the frequency dispersion of the storage modulus measurement. These observations suggest a coexistence of martensite and strain glass phases in a well-controlled composition of the Ti50- x Ni50+ x system with 1.0 ≤ x ≤ 1.3. It is revealed that the crossover from martensite to strain glass in Ti50- x Ni50+ x SMAs is mediated via a coexisting of these two phases, which are triggered by a competing interaction between the thermodynamic and kinetic processes at low temperatures. Highlights: Physical properties of Ti50- x Ni50+ x shape memory alloys for x = 1.0–1.3 were studied. A signature of martensitic transition was observed in the x = 1.1, 1.2 samples. Frequency dispersion storage modulus in the x = 1.2 sample exhibits strain glass behavior. Coexisting of martensite and strain glass phases in Ti50- x Ni50+ x alloys for x = 1.2. A modified phase diagram of the Ti50- x Ni50+ x shape memory alloys is proposed.